2008
DOI: 10.1017/s0025315408000507
|View full text |Cite
|
Sign up to set email alerts
|

Harbour porpoise (Phocoena phocoena) foraging strategy at a high energy, near-shore site in south-west Wales, UK

Abstract: Harbour porpoises (Phocoena phocoena) visit Ramsey Sound at specific states of tide to feed. The preferred foraging location is high-energy habitat in South Ramsey Sound where a tide race, overfalls and upwelling zones form during the ebb phase. Seabed topography and tidal currents combine to create a foraging resource exploited by harbour porpoises at regular and predictable intervals. Porpoises are observed surfacing repeatedly directly into the tidal stream above and adjacent to, a steep-sided trench on the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

9
52
1
2

Year Published

2008
2008
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 59 publications
(64 citation statements)
references
References 7 publications
9
52
1
2
Order By: Relevance
“…For example, although harbour porpoises are known to eat a wide variety of prey across their entire range, their diet tends to be dominated by only 2 to 4 main prey species in any given area ). There are consistent reports of the associations of harbour porpoises with dynamic, high productivity zones such as upwellings or high energy coastal locations (see for example Watts & Gaskin 1985, Borges & Evans 1997, Weir & O'Brien 2000, Johnston et al 2005, Tynan et al 2005, Pierpoint 2008). Such ephemeral aggregations of prey may be particularly important for the harbour porpoise owing to its small body reserves, cold living environment and energetically demanding reproductive schedule (Read & Westgate 1997, Reed et al 2000, Read 2001, Lockyer 2003, Johnston et al 2005.…”
Section: Abstract: Generalized Additive Models · Phocoena Phocoena ·mentioning
confidence: 69%
See 3 more Smart Citations
“…For example, although harbour porpoises are known to eat a wide variety of prey across their entire range, their diet tends to be dominated by only 2 to 4 main prey species in any given area ). There are consistent reports of the associations of harbour porpoises with dynamic, high productivity zones such as upwellings or high energy coastal locations (see for example Watts & Gaskin 1985, Borges & Evans 1997, Weir & O'Brien 2000, Johnston et al 2005, Tynan et al 2005, Pierpoint 2008). Such ephemeral aggregations of prey may be particularly important for the harbour porpoise owing to its small body reserves, cold living environment and energetically demanding reproductive schedule (Read & Westgate 1997, Reed et al 2000, Read 2001, Lockyer 2003, Johnston et al 2005.…”
Section: Abstract: Generalized Additive Models · Phocoena Phocoena ·mentioning
confidence: 69%
“…Johnston et al (2005) showed that focal regions of tagged animals tracked by satellite overlapped with localized fronts where herring Clupea harengus and euphausiid zooplankton aggregate, and that a large eddy and a frontal system extended to these areas (see also Watts & Gaskin 1985, Read & Westgate 1997. In Pem brokeshire, foraging hotspots in the vicinity of islands (Pierpoint 2001(Pierpoint , 2008) may indicate a similar process, as was found within Mousa Sound, southeast Shetland Islands (Borges & Evans 1997). …”
Section: Discussionmentioning
confidence: 88%
See 2 more Smart Citations
“…A number of papers in the present volume investigated the effects upon marine mammals of particular human activities, including ship strikes on large whales (particularly fin whale and grey whale) in the Pacific north-west of the United States (Douglas et al, 2008); disturbance from high-speed pleasure craft on bottlenose dolphins in the Mississippi Sound (USA) (Miller et al, 2008); incidental capture of Amazonian manatee calves in shrimp trawls and gillnets in NE Brazil (De Meirelles, 2008) (Pierpoint, 2008). Information on cetacean habitat requirements can help us to understand niche partitioning between species, as well as shifts in distribution related to climate variation and change.…”
mentioning
confidence: 99%